Biofortification of cowpea beans (Vigna unguiculata L. Walp) with zinc: effect on yield and mineral content - Estrada Domínguez, Verónica; Márquez Quiroz, César; de la Cruz Lázaro, Efraín; Osorio Osorio, Rodolfo; Sánchez Chávez, Esteban (Revista Mexicana de Ciencias Agrícolas, 2018)
Zinc is an essential element in biological systems, which is required in small quantities. The objective was to know the effect of the foliar application of the doses of 0, 7, 14 and 28 mM L-1 of chelate (Zn-EDTA) and zinc sulfate (ZnSO4) in the yield and mineral content of cowpea (Vigna unguiculata L.). In plants were counted the days to flowering, weight of grain, number of pods and number of grains per plant, in addition to the weight of 100 grains, while in the grains the content of total crude protein, nitrogen, phosphorus, potassium, calcium, magnesium, iron, zinc, boron, manganese, copper and molybdenum was determined. With the doses of 7, 14 and 28 mM L-1 of Zn-EDTA the yield of grain per plant with respect to the control was increased by 53.29, 41.58 and 38.42%, respectively, while with the same doses of ZnSO4 the increase it was 27.80, 32.09 and 16.83%, respectively. The highest contents of nitrogen, crude protein, phosphorus, potassium, calcium, iron, manganese and copper were obtained with the doses of 7 and 14 mM L-1 of Zn-EDTA. While the highest levels of zinc, boron, molybdenum and magnesium were found with the doses of ZnSO4, it was observed that the zinc content increases proportionally with the increase in the dose. The addition of different doses of Zn-EDTA and ZnSO4 for the biofortification of cowpea beans has an effect on grain yield, crude protein content and mineral content.
Keywords: dosage, legumes, protein, chelates, sulfates.